The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.quageo.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of termite bioturbation in a savannah ecosystem: Application of OSL dating

Abstract: Luminescence dating is one of the most promising techniques available for studying bioturbation on pedological timescales. In this study, we use multi-grain and single-grain quartz OSL to quantify termite bioturbation processes (Macrotermes natalensis) in a savannah ecosystem in Ghana. Termites transport soil from depth to the surface to construct termitaria. Over time, erosion levels these mounds and returns the sediment to the soil surface. These two processes of construction and erosion together represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…A numerical model of this process matched field observations. Kristensen et al () used a similarly novel approach to quantify the soil mixing as a “soil conveyor” driven by termite mount construction in Ghana. Gliganic et al () used a slightly different method by observing the proportion of light‐exposed grains versus depth and by calculating a downward mixing rate based on soil replacement time, an approach like those used in soil science (Richards, ; Wilkinson et al, ).…”
Section: Previous Research On Luminescence As a Sediment Tracermentioning
confidence: 99%
See 1 more Smart Citation
“…A numerical model of this process matched field observations. Kristensen et al () used a similarly novel approach to quantify the soil mixing as a “soil conveyor” driven by termite mount construction in Ghana. Gliganic et al () used a slightly different method by observing the proportion of light‐exposed grains versus depth and by calculating a downward mixing rate based on soil replacement time, an approach like those used in soil science (Richards, ; Wilkinson et al, ).…”
Section: Previous Research On Luminescence As a Sediment Tracermentioning
confidence: 99%
“…The third is to apply a probabilistic model of rarefied sand grains and use the change in single grain luminescence ages versus depth to infer timescales of particle motion and soil Peclet numbers (Furbish, Roering, Almond, et al, , Furbish, Roering, Keen‐Zebert, et al, , 2018c). An additional method is to perform a regression of age versus depth to obtain an accumulation rate to track the movement of sediment (e.g., Bruening‐Madsen et al, ; Kristensen et al, ). The choice of method is dependent on the question at hand.…”
Section: Previous Research On Luminescence As a Sediment Tracermentioning
confidence: 99%
“…Thomsen et al, 2003), some authors argue for strict rejection criteria (e.g., Yoshida et al, 2000;Jacobs et al, 2006, and references therein) based essentially on the response of grains to a number of quality-insurance tests of the SAR protocol, such as recycling, recuperation and IR depletion ratios (Murray and Wintle, 2000;2003;Wintle and Murray, 2006;Duller, 2003). Others have reported that the main effect of such rejection criteria is to reduce the number of selected grains with negligible effects on the estimated D e and overdispersion (OD) parameters, which might thus lead to a loss of robustness in the final results (e.g., Thomsen et al, 2012;Guérin et al, 2015a;Geach et al, 2015;Hansen et al, 2015;Kristensen et al, 2015;Zhao et al, 2015;Thomsen et al, 2016).…”
Section: Quartz Single Grain Oslmentioning
confidence: 99%
“…To be specific, different studies have reported a clear feedback between chemical weathering and physical erosion rates (Riebe et al, 2003;Larsen et al, 2014). Heimsath et al (2002) have shown that single-grain optically stimulated luminescence (OSL) dating offers an efficient solution for quantifying pedogenic processes such as soil mixing, erosion or deposition rates at a centennial to millennial resolution, and the approach was adopted in a number of studies in different environments (Stockmann et al, 2013;Johnson et al, 2014;Kristensen et al, 2015;Gliganic et al, 2016). Thus, there is an urgent need in soil geomorphology for complementary reconstruction methods to: (i) quantify soil fluxes related to bioturbation, (ii) elucidate soil process rates at a higher temporal resolution than is currently possible with TCN and (iii) study soil-landscape processes under non-steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%